Characterization of regular polyamide 6.6 and biodegradable polyamide 6.6 (Revista de Ensino em Artes, Moda e Design, 2025)
This study aimed to conduct a comparative analysis of conventional polyamide 6.6 and biodegradable polyamide 6.6, focusing on their physicochemical properties. To achieve this, a literature review was carried out, along with technical visits and interviews (involving qualitative data collection from industry professionals) with the Brazilian producer of both fibers (Rhodia, part of the Solvay Group). Additionally, laboratory tests were conducted on yarns and knitted fabrics made from these two poliamides. The tests included breaking elongation, tenacity, moisture regain, and fabric weight measurements, and FTIR-ATR spectroscopy. The results did not reveal significant differences. Although biodegradable polyamide 6.6 promises environmental benefits, these could not be confirmed within the scope of this study. It is concluded that further research is necessary to validate its sustainable impact in practice.
Keywords: polymers; sustainability; biodegradation